Code Switching and Code Mixing in Sacha Stevenson’s YouTube Content: A Functional Analysis for Language Learning - Nungki, Nungki; Hakim, M. Arif Rahman; Febriani, Hanura (Yayasan Sembilan Pemuda Indonesia, 2025)
This study aims to analyze the use of code switching and code mixing in Sacha Stevenson’s YouTube videos and examine their function in supporting informal English language learning. Employing a qualitative descriptive approach, the researchers analyzed three selected videos containing bilingual interactions in English and Indonesian. The data were interpreted using Poplack’s (1980) theory of code switching, Muysken’s (2000) theory of code mixing, and Gumperz’s (1972) framework for sociolinguistic functions. The results reveal that intra-sentential code switching (47%) is the most frequently used, followed by inter-sentential (38%) and tag switching (15%). In terms of code mixing, insertion (50%) dominates, with alternation (43%) and congruent lexicalization (7%) appearing less frequently. These linguistic features serve as tools for increasing accessibility, contextual comprehension, and learner engagement, particularly for audiences in bilingual environments. The study contributes to the understanding of how bilingual content in digital media can serve as an effective medium for informal language acquisition. Practically, the findings suggest that educators and content creators can leverage bilingual discourse strategically to enhance language learning experiences. While the study is limited to a small sample and lacks quantitative analysis, it lays the groundwork for future research on the pedagogical value of code switching and mixing in online platforms.